2011
DOI: 10.1186/1471-2334-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and monomicrobial necrotizing fasciitis: gram-positive versus gram-negative pathogens

Abstract: BackgroundMonomicrobial necrotizing fasciitis is rapidly progressive and life-threatening. This study was undertaken to ascertain whether the clinical presentation and outcome for patients with this disease differ for those infected with a gram-positive as compared to gram-negative pathogen.MethodsForty-six patients with monomicrobial necrotizing fasciitis were examined retrospectively from November 2002 to January 2008. All patients received adequate broad-spectrum antibiotic therapy, aggressive resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 22 publications
5
60
1
Order By: Relevance
“…We could not identify possible predisposing factors leading to the E. coli infection, i.e., receiving Gram-positive active antibiotics prior to the presentation. The reported incidence of E. coli as a monomicrobial pathogen resulting in necrotizing fasciitis is very rare, ranging from 0 to 10% (1,6,11,12). Chen et al (4) reported on 126 patients with a single etiologic agent causing necrotizing fasciitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not identify possible predisposing factors leading to the E. coli infection, i.e., receiving Gram-positive active antibiotics prior to the presentation. The reported incidence of E. coli as a monomicrobial pathogen resulting in necrotizing fasciitis is very rare, ranging from 0 to 10% (1,6,11,12). Chen et al (4) reported on 126 patients with a single etiologic agent causing necrotizing fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…Among Gram negatives, Vibrio vulnificus and Aeromonas hydrophila are well-known causative agents of monomicrobial necrotizing fasciitis (12). E. coli has been isolated from polymicrobial or Fournier's gangrene, but has rarely been reported in monomicrobial necrotizing fasciitis (8).…”
mentioning
confidence: 99%
“…Diabetic neuropathy further increases the risk of injuries, which are very often the triggering factors in cases of necrotizing fasciitis. Pre-existing chronic liver dysfunction, chronic renal failure, thrombocytopenia, hypoalbuminemia, and postoperative dependence on mechanical ventilation represent poor prognostic factors in monomicrobial necrotizing fasciitis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other prior studies have shown that there is no difference in the mortality rates of gram-positive pathogens (9.09%) and gramnegative pathogens (17.14%; p = 1.00) in monomicrobial infections, suggesting that S. pyogenes is no more virulent in necrotizing infections than are organisms such as E. coli or B. fragilis [38].…”
Section: Discussionmentioning
confidence: 81%